2017
DOI: 10.1093/hmg/ddx020
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous mutation in TRIM36 causes autosomal recessive anencephaly in an Indian family

Abstract: Anencephaly (APH) is characterized by the absence of brain tissues and cranium. During primary neurulation stage of the embryo, the rostral part of the neural pore fails to close, leading to APH. APH shows a heterogeneous etiology, ranging from environmental to genetic causes. The autosomal recessive inheritance of APH has been reported in several populations. In this study, we employed whole-exome sequencing and identified a homozygous missense mutation c.1522C > A (p.Pro508Thr) in the TRIM36 gene as the caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…[8][9][10] The etiology of CNS anomalies is multifactor and involves complex interactions between genetic and environmental factors, constituting one of the most common congenital defects. 9,21,22 Among the anomalies of the CNS observed in this study, hydrocephalus and anencephaly were the most reported changes, which is similar to other studies that also reported hydrocephalus 8,14,17,23 and the anencephaly 8,15,17,24 among the most common malformations.…”
Section: Discussionsupporting
confidence: 90%
“…[8][9][10] The etiology of CNS anomalies is multifactor and involves complex interactions between genetic and environmental factors, constituting one of the most common congenital defects. 9,21,22 Among the anomalies of the CNS observed in this study, hydrocephalus and anencephaly were the most reported changes, which is similar to other studies that also reported hydrocephalus 8,14,17,23 and the anencephaly 8,15,17,24 among the most common malformations.…”
Section: Discussionsupporting
confidence: 90%
“…A recent meta-analysis suggested maternal smoking during pregnancy as a high-risk factor for neural tube defects 36 . TRIM36 is expressed in the developing brain and is thought to be indispensable for somite formation 37 ; lack of TRIM36 due to a homozygous mutation has been reported to result in autosomal recessive anencephaly 38 . Recently, TRIM36 hypermethylation has been linked to a cell-transformation effect of Benzo[a]pyrene, a polycyclic aromatic hydrocarbon found in tobacco smoke, in bronchial epithelial cells 39 .…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] The etiology of CNS malformations is multifactorial, involving complex interactions between genetic and environmental factors, constituting one of the most common congenital defects. 22,24,25 Sunitha et al 22 analyzed 360 pregnant women with fetuses presenting structural abnormalities, and also observed a higher frequency of CNS anomalies (37%), followed by genitourinary system abnormalities (20%) and multiple CAs (11%). In addition, other studies have shown the higher prevalence of genitourinary system malformations and of genitourinary system malformations.…”
Section: Discussionmentioning
confidence: 99%